Munidopsis antonii - Baba, Keiji; Macpherson, Enrique; Poore, Gary C. B.; Ahyong, Shane T.; Bermudez, Adriana; Cabezas, Patricia; Lin, Chia-Wei; Nizinski, Martha; Rodrigues, Celso; Schnabel, Kareen E. (Zenodo, 2008)
Munidopsis antonii (Filhol, 1884) Galathodes antonii Filhol, 1884: 230, fig. 2 (NE of Azores, 3975–4010 m). Munidopsis antonii . — Henderson, 1888: 151, pl. 18, figs 1, 1a (SW of Australia, and off Juan Fernandez, 2516–3294 m). — Luke, 1977: 28 (list; Baja California, Basin off Bahia Magdalena, and off St San Juan, Peru, 3427–3676 m). — Baba, 1982a: 113, pl. 1, fig. 2 (Izu Shoto, Japan, 3420–3960 m)). — de Saint Laurent, 1985: table 2 (Bay of Biscay, 3992–4510 m). — Hendrickx & Harvey, 1999: 376 (list). — d'Udekem d'Acoz, 1999: 166 (review of occurrences). — Davie, 2002: 65 (no record). — Baba, 2005: 284 (132, 284, figs 52–54 (Mozambique Channel, off Sri Lanka, Tasman Sea, off Zamboanga, W of Costa Rica, and Gulf of Panama, 3660–3800 m, key, synonymies). — Macpherson & Segonzac, 2005: 14 (NE Atlantic, off Namibia, Gulf of Guinea, off South Africa, Azores, NW Atlantic, Bay of Biscay, 3134–4460). — Macpherson, 2007: 38 (west of Sri Lanka, 3450–3625 m). — Jones & Macpherson, 2007: 480 (off California, 4100 m). — Osawa & Takeda, 2007: 137, fig. 3C, D (south of Tosa Bay, 2739–3278 m). Munidopsis Antonii . — A. Milne Edwards & Bouvier, 1900: 321, pl. 4, fig. 2, pl. 30, figs 20–24 (N and NE of Azores, 3975–4010 m). — Hansen, 1908: 38, pl. 3, figs 3a, 3b (southern part of Davis Straits, 2626 m). — Bouvier, 1922: 47 (Bay of Biscay, 3910 m). Munidopsis beringana Benedict, 1902: 279, fig. 23 (type locality: Bering Sea, [55°23´00”N, 170°31´00”W], 3241 m [3 female syntypes, USNM 20557]). — Rathbun, 1904: 167 (no record). — Makarov, 1938: 101, fig. 36 (Sea of Okhotsk, 3500 m). — Ambler, 1980: 24 (Cascadia Basin and Tufts Plain off Oregon, 2800–3990 m). — Wicksten, 1989: 315 (list). — Chevaldonné & Olu, 1996: 290 (no record). — Martin & Haney, 2005: 478 (hydrothermal vents and cold seeps review). Munidopsis antoni [lapsus]. — Haig, 1955: 40 (no record). — Andrade, 1985: 111 (Juan Fernandez islands). Type data: syntypes, 2 males, MNHN Ga 277 and 278; 1 ovigerous female, USNM 22909. Type locality: NE of Azores, 3975–4010 m. : Published as part of Baba, Keiji, Macpherson, Enrique, Poore, Gary C. B., Ahyong, Shane T., Bermudez, Adriana, Cabezas, Patricia, Lin, Chia-Wei, Nizinski, Martha, Rodrigues, Celso & Schnabel, Kareen E., 2008, Catalogue of squat lobsters of the world (Crustacea: Decapoda: Anomura-families Chirostylidae, Galatheidae and Kiwaidae), pp. 1-220 in Zootaxa 1905 (1) on page 132, DOI: 10.11646/zootaxa.1905.1.1, http://zenodo.org/record/5134587 : {"references": ["Filhol, H. (1884) Explorations sous-marines. Voyage du Talisman. La Nature, Paris, 12, 119 - 122, 134 - 138, 147 - 151, 161 - 164, 182 - 186, 198 - 202, 230 - 234, 278 - 282, 326 - 330, 391 - 394.", "Henderson, J. R. (1888) Report on the Anomura collected by H. M. S. Challenger during the years 1873 - 76. Report on the Scientific Results of the Voyage of H. M. S. Challenger during the years 1873 - 76. Zoology, 27, 1 - 221, 21 pls.", "Luke, S. R. (1977) Catalog of the benthic invertebrate collections of the Scripps Institution of Oceanography. I - Decapod Crustacea and Stomatopoda. Scripps Institution of Oceanography Reference Series, 77 - 9, 1 - 72.", "Baba, K. (1982 a) Deep-sea galatheidean Crustacea (Decapoda, Anomura) taken by the R / V Soyo-Maru in Japanese waters. II Family Galatheidae. Bulletin of the National Science Museum, Tokyo. Series A, 8, 103 - 120.", "de Saint Laurent, M. (1985) Remarques sur la distribution des crustaces decapodes. Pp. 469 - 478 i n: Laubier, L. & Monniot, C. (Eds.) Peuplements profonds du Golf de Gascogne campagnes BIOGAS. Institut Francais de Recherche pour l'Exploitation de la Mer: Paris.", "Hendrickx, M. E. & Harvey, A. W. (1999) Checklist of anomuran crabs (Crustacea: Decapoda) from the eastern tropical Pacific. Belgian Journal of Zoology, 129, 363 - 389.", "d'Udekem d'Acoz, C. (1999) Inventaire et distribution des crustaces decapodes de l'Atlantique nord-oriental, de la Mediterranee et des eaux continentales adjacentes au nord de 25 \u00b0 N. Patrimoines naturels (M. N. H. N. / S. P. N.), 40, 1 - 383.", "Davie, P. J. F. (2002) Crustacea: Malacostraca: Eucarida (Part 2): Decapoda - Anomura, Brachyura. CSIRO Publishing, Melbourne, xiv + 641 pp.", "Baba, K. (2005) Deep-sea chirostylid and galatheid crustaceans (Decapoda: Anomura) from the Indo-West Pacific, with a list of species. Galathea Reports, 20, 1 - 317.", "Macpherson, E. & Segonzac, M. (2005) Species of the genus Munidopsis (Crustacea, Decapoda, Galatheidae) from the deep Atlantic Ocean, including cold-seep and hydrothermal vent areas. Zootaxa, 1095, 1 - 60.", "Macpherson, E. (2007) Species of the genus Munidopsis Whiteaves, 1784 from the Indian and Pacific Oceans and reestablishment of the genus Galacantha A. Milne-Edwards, 1880 (Crustacea, Decapoda, Galatheidae). Zootaxa, 1417, 1 - 135.", "Jones, W. J. & Macpherson, E. (2007) Molecular phylogeny of the East Pacific squat lobsters of the genus Munidopsis (Decapoda: Galatheidae) with the descriptions of seven new species. Journal of Crustacean Biology, 27, 477 - 501.", "Osawa, M. & Takeda, M. (2007) Deep-sea Galatheidae (Crustacea, Decapoda, Anomura) from Tosa Bay and Okinawa Trough, Southern Japan. Bulletin of the National Museum, of Natural Science, Tokyo, Series A, 33, 133 - 146.", "Milne Edwards, A. & Bouvier, E. L. (1900) Crustaces decapodes. Premiere partie. Brachyures et Anomoures. In: Milne- Edwards, A. (Ed.) Expeditions scientifiques du Travailleur et du Talisman pendant les annees 1880, 1881, 1882, 1883. Masson, Paris, pp. 1 - 396, 32 pls.", "Hansen, H. J. (1908) Crustacea Malacostraca I. Danish Ingolf Expedition, 3, 1 - 120, pls 1 - 5.", "Bouvier, E. L. (1922) Observations complementaires sur les crustaces decapodes (Abstraction faite des Carides) provenant des Campagnes de S. A. S. le Prince de Monaco. Resultats des Campagnes Scientifiques accomplies sur son Yacht par Albert Ier Prince Souverain de Monaco, 62, 1 - 106, pls 1 - 6.", "Benedict, J. E. (1902) Description of a new genus and forty six new species of crustaceans of the family Galatheidae with a list of the known marine species. Proceedings of the Biological Society of Washington, 26, 243 - 334.", "Rathbun, M. J. (1904) Decapod crustaceans of the northwest coast of North America. Vol. 10. Crustaceans in: Rathbun, M. J., Richardson, H., Holmes, S. J. & Cole, L. J. (Eds.) Harriman Alaska Expedition with cooperation of Washington Academy of Sciences. Alaska. Doubleday, Page & Co, New York, pp. 1 - 200.", "Makarov, V. V. (1938) Anomura. Rakoobraznyey, Vol. 10, No. 3. In: Shtakel'berg, A. A. (ed.), Fauna SSSR, (new series) 16, x + 324 pp., 5 pls. Academii Nauk SSSR, Moscow (English translation, 1962: Crustacea, Anomura. Jerusalem: Israel Program for Scientific Translation. 278 pp.)", "Ambler, J. W. (1980) Species of Munidopsis (Crustacea, Galatheidae) ocurring off Oregon and in adjacent waters. Fishery Bulletin, 78, 13 - 34.", "Wicksten, M. K. (1989) Ranges of offshore decapod crustaceans in the eastern Pacific Ocean. Transactions of the San Diego Society of Natural History, 21, 291 - 316.", "Chevaldonne, P. & Olu, K. (1996) Ocurrence of anomuran crabs (Crustacea: Decapoda) in hydrothermal vent and coldseep communities: A review. Proceedings of the Biological Society of Washington, 109, 286 - 298.", "Martin, J. W. & Haney, T. A. (2005) Decapod crustaceans from hydrothermal vents and cold seeps: a review through 2005. Zoological Journal of the Linnean Society, 145, 522.", "Haig, J. (1955) Reports of the Lund University Chile Expedition 1948 - 49. 20. The Crustacea Anomura of Chile. Lunds Universtitets Arsskrift N. F. Avd. 2, 51, 1 - 68.", "Andrade, H. (1985) Crustaceos decapodos marinos del Archipielago de Juan Fernandez. In: Arana, P. (Ed.) Investigaciones marinas en el Archipielago de Juan Fernandez. Chile. Universidad Catolica de Valparaiso, Valparaiso, pp. 109 - 116."]}